In Vitro Cytotoxic Effects of Some Fumaria L. (Papaveraceae) Species Methanolic Extracts on Cancer Cell Lines - Sancar, Pelin Yılmaz; Taskin, Irmak Icen (My University, 2024)
The Fumaria L. species (Papaveraceae), is known colloquially as “Şahtere”. This species, which has been proven to contain significantly rich components, is used by people to treat a number of different diseases. This study investigated the cytotoxic effects of the methanolic extracts of above-ground portions of Fumaria asepala Boiss. and Fumaria schleicheri Soy.-Will. subsp. microcarpa Boiss. ex Hausskn. taxons against Beas-2B, sh-sy5, HCT116 and A549 cell lines. The changes in cancer cell vitality were identified using the 3-(4.5-dimethylthiazol -2-il)-2.5-diphenyltetrazolium bromide (MTT). While the results showed that F. asepala and F. schleicheri subsp. microcarpa's methanolic extracts presented a meaningful decrease in the vitality of colon (HCT-116) cancer cells, no cytotoxic effect was achieved on lung (A549) cancer and brain (sh-sy5) cancer cells. Also, the herbal extracts did not create any toxic effect on healthy lung cells (Beas-2B).
Keywords: A549; Fumaria; Cytotoxic; Beas-2B; sh-sy5; HCT116